Age Management in the Brazilian Context: A Theoretical Discussion - da Silva, Mayara Andresa Pires; Helal, Diogo Henrique (Organizations and Markets in Emerging Economies, 2022)
The aging of population and workforce has significantly impacted living conditions in society and organizations around the world. This scenario represents a challenge for public policymakers and for the labor market, whose future depends on the maintenance of the work capacity of the older workers and their continued participation in the labour market. In this context, age management policies are increasingly important as they play a crucial role in increasing and sustaining the participation of these workers in the labor market. This theoretical essay aims to discuss age management in the Brazilian context. Specifically, it seeks to present the concept of age management and its challenges for the organizations in Brazil. Age management has been defined as the best way to strategically deal with the changes resulting from the aging of the population and consequent changes in the labor market. We argue, in this study, that the phenomenon of aging has specific characteristics in Brazil, a country with a collectivist trait in which intergenerational affective-moral-financial responsibility is the main issue.